Is acute glaucoma a symptom of diabetes?. Issue 12 (December 1986) - Clarke, M.; Jagger, J.
Abstract : Forty-three patients who had suffered an episode of angle closure glaucoma had an assessment of glucose tolerance. Two patients were known diabetics and one new diabetic was found as a result of the study. The prevalence of diabetes in this series did not differ significantly from the normal in view of the age distribution of the patients.